The impact of pollution taxation on competitive green product choice strategies. (November 2019) - Yu, Wei; Han, Ruizhu
Highlights: We explore game structure and pollution taxation impacts on product choices. We consider two duopoly supply chains with two competing manufacturers. For equal power, they choose regular or green products under high and low tax. Otherwise, they choose regular or green products simultaneously under moderate tax. Abstract: This paper explores the impact of game structure and pollution taxation on the product choice strategies of two duopoly supply chains with two competing manufacturers. We address two game structures, namely a Stackelberg game with one dominant manufacturer and a power balanced Nash game. In the Stackelberg game with one dominant manufacturer, the decision of following the manufacturer is made on the basis of the manufacturer being the Stackelberg leader, while in the power balanced Nash game, the two manufacturers make decisions simultaneously. Our analytical results show that (1) if the two manufacturers have equal bargaining power in determining product choices as well as deciding prices, they will both always choose regular products at equilibrium under a low pollution taxation rate and green products under a high pollution taxation rate. However, if they have asymmetrical bargaining power in determining prices, only the follower manufacturer will choose green products under a low pollution taxation rate and both will choose green products under the high pollution taxation rate. (2) If the two manufacturers have asymmetrical bargaining power in making product choice decisions, the results are similar to those of point (1), except that the two manufacturers will arbitrarily choose ordinary or green products under a moderate pollution taxation rate if they make simultaneous price decisions. Our research also suggests that, to abate product environmental pollution, governments have to introduce a higher pollution taxation rate, regardless of the power structure between manufacturers, to encourage them to produce greener products and increase supply chain members' profits.